Ethnic-Cultural Bullying Versus Personal Bullying: Specificity and Measurement of Discriminatory Aggression and Victimization Among Adolescents - Rodríguez-Hidalgo, Antonio J.; Calmaestra, Juan; Casas, José A.; Ortega-Ruiz, Rosario (Frontiers in Psychology, 2019)
The present study contrasts personal bullying with ethnic-cultural bullying. A representative pluricultural sample from a Spanish adolescent population of Secondary Education took part in the study (N=27369). The sample filled in the EBIPQ to measure the personal bullying. Additionally, they filled in an adaptation of this questionnaire to measure the ethnic-cultural bullying: the EBIPQ-ECD. The EBIPQ-ECD validation showed optimal psychometric properties and a bidimensional structure: ethnic-cultural victimization and ethnic-cultural aggression. The same roles of participation in personal bullying —aggressor, victim, bully/victim, non-involved— were observed in ethnic-cultural bullying, but they did not coincide with each other in a considerable part. Therefore, we concluded that ethnic-cultural bullying is a different phenomenon from personal bullying, with the possibility of existing certain dynamism between both. To prevent and mitigate ethnic-cultural bullying, educational inferences are proposed. We also recommend the use of the EBIPQ-ECD as a tool to evaluate and detect ethnic-cultural aggressions and victimization.